2013
DOI: 10.1038/aps.2013.84
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide suppresses the expression of MMP-8, MMP-13, and TIMP-1 in left ventricles of rats with cardiac volume overload

Abstract: Aim: To study the effects of hydrogen sulfide (H 2 S) on the left ventricular expression of MMP-8, MMP-13, and TIMP-1 in a rat model of congenital heart disease. Methods: Male SD rats underwent abdominal aorta-inferior vena cava shunt operation. H 2 S donor NaHS (56 μmol·kg -1 ·d -1, ip) was injected from the next day for 8 weeks. At 8 weeks, the hemodynamic parameters, including the left ventricular systolic pressure (LVSP), the left ventricular peak rate of contraction and relaxation (LV±dp/dt max ) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In the present study, cell collagen production induced by SPCP treatment was 30-142% higher compared with the control group. The expression levels of the collagen-degrading protein MMP-8, which serves as a key enzyme in the degradation of collagen and stimulates the degradation of other major dermal components (which subsequently leads to aging) (41), was investigated by western blot analysis. These were decreased significantly in a dose-dependent manner in cells treated with SPCP.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, cell collagen production induced by SPCP treatment was 30-142% higher compared with the control group. The expression levels of the collagen-degrading protein MMP-8, which serves as a key enzyme in the degradation of collagen and stimulates the degradation of other major dermal components (which subsequently leads to aging) (41), was investigated by western blot analysis. These were decreased significantly in a dose-dependent manner in cells treated with SPCP.…”
Section: Discussionmentioning
confidence: 99%
“…Reversely, in mice cardiac tissues obtained following myocardial infarction, the observed decrease in CSE expression was associated with an increase in MMPs [ 30 ]. Other studies have also demonstrated that exogenous H 2 S sources (NaHS) led to reduction of MMP-13 and/or MMP-8 levels in human chondrocytes under inflammatory conditions [ 14 ] and in a model of rat heart disease [ 31 ].…”
Section: Discussionmentioning
confidence: 99%